New synthetic benzisoxazole derivatives as antimicrobial, antioxidant and anti-inflammatory agents - Shivaprasad, Chalya Mallappaji; Jagadish, Swamy; Swaroop, Toreshettahally Ramesh; Mohan, Chakrabhavi Dhananjaya; Roopashree, Rangaswamy; Kumar, Kothanahally Shivaramu Sharath; Rangappa, Kanchugarakoppal Subbegowda (European Journal of Chemistry, 2013)
A series of piperidine conjugated benzisoxazole derivatives were synthesized and evaluated for their antibacterial, anti-oxidant and anti-inflammatory activities. The results showed that most of the tested compounds exhibit good to moderate antimicrobial activity against some strains of Gram negative bacteria (Escherichia coli, Klebsiella pneumoniae, Salmonella typhi, Shigella flexineri) and Gram positive bacteria (Bacillus subtilis). Further, the molecules were evaluated for anti-oxidant assays such as DPPH scavenging, super oxide radical scavenging and hydroxyl radical scavenging assays. Most of the compounds showed potent antioxidant activities. Also, the synthesized compounds were screened for anti-inflammatory activities such as lipoxygenase inhibition and indirect haemolytic assays, where compounds revealed good activity.